Adiposity Phenotypes and Subclinical Atherosclerosis in Adults from Sub–Saharan Africa: An H3Africa AWI–Gen Study. Issue 1 (19th March 2021) - Nonterah, Engelbert A.; Bots, Michiel L.; Oduro, Abraham; Agongo, Godfred; Soo, Cassandra C.; Micklesfield, Lisa K.; Mashinya, Felistas; Boua, Palwendé R.; Mohamed, Shukri F.; Wade, Alisha N.; Kyobutungi, Catherine; Tinto, Halidou; et al.
Background: Obesity and adipose tissue distribution contribute to an increased risk of cardiovascular disease (CVD) by promoting atherosclerosis. This association has been poorly studied in sub–Saharan Africa (SSA) despite the rising prevalence of cardiovascular disease. Objectives: We determined the association between various adiposity phenotypes and carotid intima–media thickness (CIMT), a proxy of subclinical atherosclerosis, in a large SSA population. Methods: A population–based cross–sectional study was performed from 2013–2016 in Burkina Faso, Ghana, Kenya and South Africa. Body mass index (BMI), waist (WC), hip circumferences (HC), visceral (VAT) and subcutaneous adipose tissue (SCAT) using B-mode ultrasound were measured. Ultrasonography of left and right far wall CIMT of the common carotid artery was used as an indicator of subclinical atherosclerosis. Individual participant data meta–analyses were used to determine the associations between adiposity phenotypes and CIMT in the pooled sample while adjusted multivariable linear regression analyses were used for site specific analyses. Results: Data were obtained from 9, 010 adults (50.3% women and a mean age of 50± 6years). Men had higher levels of visceral fat than women while women had higher BMI, waist and hip circumference and subcutaneous fat than men at all sites except Burkina Faso. In the pooled analyses, BMI (β–value [95% CIs]: 19.5 [16.8, 22.3] μm) showed the strongest relationship with CIMT followed by VAT (5.86 [4.65, 7.07] μm), SCAT (5.00 [2.85, 7.15] μm), WC (1.27 [1.09, 1.44] μm) and HC (1.23 [1.04, 1.42] μm). Stronger associations were observed in men than in women. Conclusion: Obesity within SSA will likely result in higher levels of atherosclerosis and promote the occurrence of cardio- and cerebrovascular events, especially in males, unless addressed through primary prevention of obesity in both rural and urban communities across Africa. The inverse association of VAT with CIMT in Burkina Faso and Ghana requires further investigation. Highlights: All adiposity phenotypes were positively associated with common carotid intima–media thickness (CIMT) in the entire cohort (pooled analyses). BMI had the strongest association with CIMT compared to other phenotypes. The magnitude of association between adiposity phenotypes and CIMT was higher in men than in women. Subcutaneous adipose tissue was inversely associated with CIMT only in women. An unexpected finding was the inverse association of visceral adipose tissue with CIMT in Burkina Faso and Ghana.